Histopathological Analysis of Tumor Microenvironment and Angiogenesis in Pheochromocytoma - Gao, Xin; Yamazaki, Yuto; Pecori, Alessio; Tezuka, Yuta; Ono, Yoshikiyo; Omata, Kei; Morimoto, Ryo; Nakamura, Yasuhiro; Satoh, Fumitoshi; Sasano, Hironobu (Frontiers in Endocrinology, 2020)
Pheochromocytomas (PHEOs) are relatively rare catecholamine-producing tumors derived from adrenal medulla. Tumor microenvironment (TME) including neoangiogenesis have been explored in many human neoplasms but not necessarily in PHEOs. Therefore, in this study, we firstly examined tumor infiltrating lymphocytes (CD4 and CD8), tumor associated macrophages (CD68 and CD163), sustentacular cells (S100p) and angiogenic markers (CD31 and areas of intratumoral hemorrhage) in 39 cases of PHEOs in the quantitative fashion. We then compared the results with pheochromocytoma of the adrenal gland scaled score (PASS), grading system for pheochromocytoma and paraganglioma (GAPP) and the status of intra-tumoral catecholamine-synthesizing enzymes (TH, DDC and PNMT) as well as the clinicopathological factors of the patients. Intratumoral CD8 (p=0.0400), CD31 (p=0.0256) and PNMT (p=0.0498) positive cells were all significantly more abundant in PHEOs with PASS < 4 than PASS ≧ 4. In addition, intratumoral CD8 positive lymphocytes were also significantly more abundant in well- than moderately differentiated PHEOs according to GAPP score (p=0.0108). Intratumoral CD68 positive cells were significantly higher in PHEOs with regular or normal histological patterns than those not (p=0.0379) and positively correlated with DDC status in tumor cells (p=0.0168). The status of CD163 was significantly positively correlated with that of CD8 positive cells (p=0.0032). The proportion of intratumoral hemorrhagic areas was significantly higher in PHEOs with PASS ≧ 4 (p=0.0172) and capsular/vascular invasion (p=0.0031) than those not. DDC immunoreactivity in tumor cells was significantly positively correlated with PASS score (p=0.0356) and TH status was significantly higher in PHEOs harboring normal histological patterns (p=0.0236) and cellular monotony (p=0.0219) than those not. Results of our present study did demonstrate that CD8 and CD31 could serve as potential prognostic markers and therapeutic targets in well-differentiated PHEOs. PHEOs with increased intratumoral hemorrhage as well as the absence of TH in tumor cells could also represent more aggressive tumors.